STUDI KASUS: PENERAPAN FOOT MASSAGE TERHADAP KUALITAS TIDUR PADA REMAJA DENGAN POST OPERASI APPENDIKTOMI DI RSUD PAKUHAJI TANGERANG - Alfu, Nadia Nur (Journal of Smart Nursing and Health Science, 2025)
Background: To treat appendicitis, appendicectomy is an invasive procedure that involves cutting out the inflamed appendix by opening the lining of the abdominal wall. Anxiety, insomnia and reduced mobility are just some of the physical and psychological side effects of postoperative pain. Non-pharmacological measures, such as therapeutic foot massage, are practiced by nurses to improve the patient's quality of sleep. Purpose: To find out how foot massage affects the sleep quality of adolescents after appendectomy. Methods: This paper uses a descriptive case study design method by applying nursing care. Results: After applying foot massage for 3 days, the final results of sleep quality between An. T and An. E have different scores, An. T from score 12 to score 7 and An. The application of foot massage is effective for improving sleep quality in patients with postoperative. Conclusion: It is possible to draw the conclusion that An's sleep patterns can be improved by applying foot massage based on the results of the two patients. An and T. E the adolescent age following appendicectomy. Suggestion: It is hoped that it can be one of the efforts that can be done if there is a problem that feels disturbed sleep patterns and pain as a first step in bringing patients to health facilities.